Respiracijske transfuzijske reakcije - Marić, Ivica (Zdravniški vestnik, 2017)
Respiratory transfusion-related reactions are not very frequent, partly also because recognition and reporting transfusion reactions is still underemphasized. This article describes the most important respiratory transfusion reactions, their pathophysiology, clinical picture and treatment strategies. Respiratory transfusion related reactions can be primary or secondary. The most important primary transfusion-related reactions are TRALI - transfusion-related acute lung injury, TACO - transfusion- associated circulatory overload, and TAD - transfusion-associated dyspnea. TRALI is immuneassociated injury of alveolar basal membrane, which becomes highly permeable and causes noncardiogenic pulmonary edema. Treatment of TRALI is mainly supportive with oxygen, fluids (in case of hypotension) and in cases of severe acute respiratory failure also mechanic ventilation. TACO is caused by volume overload in predisposed individuals, such as patients with heart failure, the elderly, infants, patients with anemia and patients with positive fluid balance. Clinical picture is that of a typical pulmonary cardiogenic edema, and the therapy is classical: oxygen and diuretics, and in severe cases also non-invasive or invasive mechanical ventilation. TAD is usually a mild reaction of unknown cause and cannot be classified as TACO or TRALI, nor can it be ascribed to patient's preexisting diseases. Although the transfusion-related reactions are not very common, knowledge about them can prevent serious consequences. On the one hand preventive measures should be sought, and on the other early recognition is beneficial, so that proper treatment can take place.
Keywords: blood components; heart failure; krvne komponente; pilmonary edema; pljučni edem; srčno popuščanje